The Relationship between Nutrition and COVID-19 Symptoms among Nursing Faculty Students - Abdulabbas, Hussein Ali; Hussein, Mohammed Abbas; Hindy, Hayder Abdul-Amir Maki Al (South Asian Journal of Social Sciences and Humanities, 2024)
The COVID-19 pandemic, declared a global health crisis by the WHO, has prompted  significant shifts in lifestyle and health behaviors worldwide. This study investigates the  relationship between dietary habits and manifestations of COVID-19 among nursing students  in the Faculty of Nursing at the University of Babylon, employing a descriptive cross-sectional  methodology. Drawing from a sample of 100 students, data was collected using a structured  questionnaire encompassing demographic information, COVID-19 symptoms, and dietary  patterns. Statistical analyses were conducted using SPSS V.23 and Excel 2016. Results  indicated a predominantly female (61%) sample, with most participants being unmarried  (64%). Common COVID-19 symptoms reported included loss of smell and taste (for one  week), cough with secretions, high temperature, and shortness of breath. The study observed  discrepancies in symptom presentation compared to previous research, highlighting variations  in manifestations among populations. Notably, individuals who consumed vegetables  demonstrated a lower risk of COVID-19 complications, suggesting a potential protective role  of vegetable intake against the virus. However, no significant correlations were found between  demographic factors and COVID-19 manifestations. Based on the findings, recommendations  are proposed to promote healthier dietary practices among individuals, emphasizing the  consumption of fresh fruits and vegetables, eggs, and nutrient-rich foods to aid in COVID-19  recovery. Additionally, suggestions include regular meal consumption, hydration, and  moderation of caffeine intake. In conclusion, this study underscores the importance of nutrition  in mitigating the impact of COVID-19 and provides valuable insights into dietary behaviors  among nursing students during the pandemic. Future research should explore longitudinal  associations between diet and COVID-19 outcomes to inform public health interventions and  preventive strategies effectively.
Keywords: COVID-19; Dietary patterns; Nutrition; Symptomatology; Disease severity